Systematic oxygen impurity reduction in smooth N-polar GaN by chemical potential control. (29th November 2021) - Szymanski, Dennis; Wang, Ke; Kaess, Felix; Kirste, Ronny; Mita, Seiji; Reddy, Pramod; Sitar, Zlatko; Collazo, Ramon
Abstract: Process chemical potential control and dislocation reduction were implemented to control oxygen concentration in N-polar GaN layers grown on sapphire substrates via metal organic chemical vapor deposition (MOCVD). As process supersaturation was changed from ∼30 to 3400, the formation energy of the oxygen point defect increased, which resulted in a 25-fold decrease in oxygen incorporation. Reducing dislocations by approximately a factor of 4 (to ∼10 9 cm −3 ) allowed for further reduction of oxygen incorporation to the low-10 17 cm −3 range. Smooth N-polar GaN layers with low oxygen content were achieved by a two-step process, whereas first a 1 µ m thick smooth N-polar layer with high oxygen concentration was grown, followed by low oxygen concentration layer grown at high supersaturation.